Preferential Market Access Design : Evidence and Lessons from African Apparel Exports to the United States and the European Union - de Melo, Jaime (Oxford University Press on behalf of the World Bank, 2015)
The least developed countries rely on preferential market access. To benefit from these preferences, proof of sufficient transformation must be provided to customs in importing countries by meeting the rules of origin requirements. These rules of origin are complicated and burdensome to exporters in least developed countries. Since 2001, under the U.S. Africa Growth Opportunity Act (AGOA), 22 African countries that export apparel to the United States have been able to use fabric of any origin (single transformation) and still meet the criterion for preferential access (the so-called Special Rule). In contrast, the EU has continued to require yarn to be woven into fabric and then made into apparel in the same country (double transformation). Panel estimates for the 1996–2004 period exploit this quasi-experimental change in the design of preferences. Estimates show that this simplification contributed to an increase in export volume of approximately 168 percent for the top seven beneficiaries, or approximately four times as much as the 44 percent growth effect from the initial preferential access under the AGOA without single transformation. This change in design was also important for diversity in apparel exports because the number of export varieties grew more rapidly under the AGOA special regime.